The impact of public interventions on self-sustainable venture capital market development in Latvia from the perspective of VC fund managers - Anita Matisone; Natalja Lace (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper presents the results of a study on the impact of EU structural funds on the development of a self-sustainable venture capital (VC) market in Latvia from the perspective of VC fund managers. The study had two objectives. The first was to assess the contribution of European Union (EU) structural funds (SF) programmes toward the development of a self-sustainable VC industry in Latvia. The second was to identify ways by which the structural fund support could be better exploited for the development of the VC industry in Latvia. During three SF planning periods, the stated primary goal of the programmes to support high-growth SMEs was attained-to date, 294 VC investments have been made by publicly supported hybrid VC funds. During the 2004-2006 planning period, the first generation of professional VC fund managers in Latvia emerged in response to the opportunity to manage publicly supported hybrid VC funds. During the subsequent programmes, a high continuation rate by the established managers was observed. Nevertheless, Latvian VC fund managers are not yet capable of raising private funds and still encounter difficulties in attracting the necessary level of private capital for the publicly supported hybrid VC funds. The novelty of the study is the finding that improvements in the SF programme designs did not significantly decrease the impact of factors identified as limiting the success of the operations of VC managers. This suggests and confirms conclusions of other studies that argue that public policies aimed at creating healthy and supporting conditions for VC activity are necessary in addition to public financial support for VC funds. Regarding the next planning period, the suggestion regarding programme design is to continue with already started improvements: increasing the volume of funds, widening the geographic area eligible for investments, reducing restrictions on the types of financial instruments that may be used, lowering the administrative burden for VC fund managers and avoiding micromanagement of VC funds by governmental agency. The observation that the influence of investments in VC funds on the governmental agency's responsible for VC investments financial statements may be partly responsible for the tendency to micromanage VC funds could be useful not only in Latvia but also in other countries.
Keywords: 650; Latvia; public interventions; venture capital